Hong Kong's Chinese History Curriculum from 1945 : Politics and Identity - Kan, Flora L. F. (Book collections on Project MUSE., 2007)
This book examines how the aims, content, teaching, learning and assessment of the Chinese history curriculum have evolved since 1945. It describes how Chinese history became an independent subject in secondary schools in Hong Kong despite the political sensitivity of the subject, how it consolidated its status during the colonial period, and how it has faced threats to its independence since the return of Hong Kong to China in 1997.